QUALITY AND SHELF LIFE OF VALUE ADDED CARABEEF LOAVES AT REFRIGERATED TEMPERATURE - R. Narendra Babu; C. Vasanthi; K. Dushyanthan; S. Ezhilvelan; M. Muthulakshmi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Value added carabeef loaves were developed with variety meat, offals and non-meat extenders (refined wheat flour-T1 and soya flour-T2) while control loaves were prepared with skeletal meat and refined wheat flour. The loaves were packed aerobically in sterile Pet/Poly packages and subjected to physic-chemical quality, microbial profile and sensory quality analysis. Incorporation of low value meat and offals did not affect the physico-chemical characteristics of the loaves as reflected by the statistical similarity between control and treatment loaves. This is further confirmed by the improved organoleptic acceptability of the treatment loaves over the control loaves. The results of total viable count and yeast and mold count reveal shelf stability of loaves for 14 days. The acceptability of T1 and T2 carabeef loaves over the control loaves concludes that low value meat and offals can be incorporated @ 25% replacement of skeletal meat and soya flour can be used as a binder in the development of value added carabeef loaves which can be stored safely up to 14 days at 4±1 °C under aerobic packaging